Pile Foundation Design for a 9-Story Office Building (Case Study: Mozia Office, South Tangerang) - Enduh, Muhammad; Agita Kabdiyono, Era (Asosiasi Dosen Muda Indonesia, 2026)
Building safety is largely determined by the ability of the foundation to transfer structural loads to soil layers with adequate bearing capacity. Therefore, in conditions where the surface soil is weak, pile foundations are used to reach more stable layers. This study evaluates the performance of pile foundations at the Mozia Office Building, a nine-storey office building in Bumi Serpong Damai, through an analysis of bearing capacity, group efficiency, and foundation settlement based on SPT data and laboratory testing with parameters of N-SPT, soil weight, porosity, and soil shear strength. The foundation capacity was calculated by separating the end bearing capacity using the Meyerhof method and the skin friction using the α method according to McClelland (1974) and Reese and Wright (1977), while the pile group efficiency was reviewed conservatively from several empirical methods and the settlement was analysed using semi-empirical methods and Vesic (1977). The analysis results indicate that the effective soil layer for pile tip placement is at a depth of approximately 10 m, with an ultimate bearing capacity of 9,153.55 kN, a permissible bearing capacity of 3,051.18 kN, and a single pile settlement of 4.43 cm and a pile group settlement of 6.27 cm, which still meet the permissible limits. Therefore, the planned pile foundation is considered safe and suitable for use.